DIRECT FOREIGN INVESTMENT DEVELOPMENT FROM EXCHANGE RATE AND GDP IN ASEAN PLUS THREE COUNTRIES - Sahdha Prakasa; Wahyu Liana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to determine the effect of interest rates, economic growth, GDP per capita and exports on foreign direct investment (FDI) in ASEAN Plus Three countries. The data used is secondary data from 2011-2020 obtained from the World Bank. The results of this study provide information to policy makers in monitoring capital inflows in terms of market transparency and highlight the importance of the stock market micro structure in assessing asymmetric information for ASEAN plus three countries.